Cytokines and microbicidal molecules regulated by IL-32 in THP-1-derived human macrophages infected with New World Leishmania species. - Jéssica Cristina Dos Santos; Bas Heinhuis; Rodrigo Saar Gomes; Michelle S M A Damen; Fernando Real; Renato A Mortara; Samuel T Keating; Charles A Dinarello; Leo A B Joosten; Fátima Ribeiro-Dias (Public Library of Science (PLoS), 2017)
BACKGROUND:Interleukin-32 (IL-32) is expressed in lesions of patients with American Tegumentary Leishmaniasis (ATL), but its precise role in the disease remains unknown. METHODOLOGY/PRINCIPAL FINDINGS:In the present study, silencing and overexpression of IL-32 was performed in THP-1-derived macrophages infected with Leishmania (Viannia) braziliensis or L. (Leishmania) amazonensis to investigate the role of IL-32 in infection. We report that Leishmania species induces IL-32γ, and show that intracellular IL-32γ protein production is dependent on endogenous TNFα. Silencing or overexpression of IL-32 demonstrated that this cytokine is closely related to TNFα and IL-8. Remarkably, the infection index was augmented in the absence of IL-32 and decreased in cells overexpressing this cytokine. Mechanistically, these effects can be explained by nitric oxide cathelicidin and β-defensin 2 production regulated by IL-32. CONCLUSIONS:Thus, endogenous IL-32 is a crucial cytokine involved in the host defense against Leishmania parasites.